MERENUNGKAN KEMBALI PROFESI GURU - Ayu Nindya Wahono; Tasya Ratri Putri; Ririn Susanti Maghdalena (Jurnal Multidisipliner Bharasa, 2023)
Education is closely related to various resources in it, including teachers. 2022 is the year of building the foundation of education by incorporating elements of technology in it. With the theme "The Transformation of Education Begins With Teachers", the commemoration of world teacher's day in 2022 emphasizes the aspect of educators as the frontline for changes in the education system. For this reason, the government needs concrete steps to support this international scale program. This paper aims to dig deeper into the education system in Indonesia, so that in the end it is able to provide an alternative discourse on reflection on the profession of a teacher. Research is a type of normative research. Data collection through literature review. Data analysis through the process of triangulation. The results of the research show that the problems of education in Indonesia still receive extraordinary support from the community, one of which is through various programs organized by groups and non-governmental organizations. This is a slap in the face for the government considering that there are still many problems in the world of education in Indonesia which often recur from time to time but are still unresolved. Keywords: Teachers, Education, National Education System Abstrak: Pendidikan lekat dengan berbagai sumberdaya yang ada di dalamnya, termasuk guru. Tahun 2022 merupakan tahun membangun pondasi pendidikan dengan memasukkan unsur teknologi di dalamnya. Dengan megusung tema “The Transformation of Education Begins With Teachers”, peringatan hari guru sedunia tahun 2022 mengedepankan aspek pendidik sebagai garda terdepan perubahan sistem pendidikan. Untuk itulah diperlukan langkah nyata pemerintah dalam mendukung program skala internasional ini. Tulisan ini bertujuan untuk menggali lebih dalam sistem pendidikan di Indonesia, hingga pada akhirnya mampu memberikan wacana alternatif refleksi profesi seorang guru. Penelitian merupakan jenis penelitian normatif. Pengumpulan data melalui kajian pustaka. Analisis data melalui proses triangulasi. Hasil penelitian menunjukkan bahwa problematika pendidikan di Indonesia masih mendapat dukungan luar biasa dari masyarakat, salah satunya melalui berbagai program yang diselenggarakan oleh kelompok maupun lembaga non pemerintahan. Hal ini merupakan tamparan bagi pemerintah mengingat masih banyaknya masalah di dunia pendidikan Indonesia yang seringkali terulang dari masa ke masa namun masih belum terselesaikan. Kata kunci: Guru, Pendidikan, Sisdiknas